1988
DOI: 10.1152/ajpendo.1988.255.2.e218
|View full text |Cite
|
Sign up to set email alerts
|

Characterization by microdialysis of intracellular glucose level in subcutaneous tissue in humans

Abstract: The subcutaneous intercellular glucose concentration was measured with a microdialysis method in 14 healthy volunteers and compared with that in venous blood. Under steady-state fasting conditions the intercellular glucose concentration was similar to that in the blood. During an oral glucose tolerance test the absorption phase was slightly delayed (approximately 2 min) in the intercellular space compared with the blood. However, the kinetics for the decline in glucose was similar in the two compartments. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 9 publications
7
65
1
Order By: Relevance
“…and s. c. glucose sensor signal. This value is comparable to most other studies on s. c. glucose measurement using microdialysis [15,16] or enzyme electrodes [17]. The pattern of the s.c. glucose concentrations obtained by our device generally paralleled the course of the blood glucose concentrations up to 21 h, demonstrating both stability of the amperometric glucose sensor and constant permeability of the microdialysis probe.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…and s. c. glucose sensor signal. This value is comparable to most other studies on s. c. glucose measurement using microdialysis [15,16] or enzyme electrodes [17]. The pattern of the s.c. glucose concentrations obtained by our device generally paralleled the course of the blood glucose concentrations up to 21 h, demonstrating both stability of the amperometric glucose sensor and constant permeability of the microdialysis probe.…”
Section: Discussionsupporting
confidence: 89%
“…Our technique has the advantage of continuously monitoring glucose in the s.c. tissue, compared to previous studies [16,21], where dialysate fractions were collected intermittantly and glucose was estimated by a laboratory method. Since a rupture of the dialysis membrane, due to a sudden movement of the subject cannot be excluded, the technique of Aalders et al [15], requiring continuous perfusion of the microdialysis tube with GOD,~ has more risks than ours.…”
Section: Discussionmentioning
confidence: 99%
“…This process is not mediated by a glucose transporter, but probably by simple transcellular and/or paracellular diffusion (4). The equilibrium kinetics between glucose in the blood and interstitium are not clear, but certainly there is a direct relationship as changes in the interstitial glucose pool are positively correlated with changes in the blood glucose pool (5). Some believe that a significant time difference exists for the equilibration of interstitial and blood glucose (i.e., a "lag time") (6).…”
mentioning
confidence: 99%
“…Most attention has been directed to adipose tissue, mainly because of easy access, and studies have reported the measurement of ECF levels of glucose, lactate and glycerol [1,[38][39][40][41][42] and characterized the opposing effects of insulin and sympathetic stimulation on adipose tissue fat and glucose metabolism [39,[43][44][45]. The application of microdialysis to the study of diabetic or insulin resistant states has been limited but work in this area includes study of the effects of insulin withdrawal [45] and hyperglycaemia [46] on levels of substrates in adipose ECF in IDDM; and abnormalities of glucose and glycerol metabolism in adipose tissue have also been reported in obesity [39,47], patients with liver cirrhosis [48] and spinal cord injured patients with mild insulin resistance [49].…”
Section: Skeletal Musclementioning
confidence: 99%